EPISTEMOLOGI AL-QURAN DALAM MEMBANGUN SAINS ISLAM - Misbahuddin, Iing (TEOLOGIA, 2015)
Abstract: This article aims to elaborate on the Quran as the basis of Islamic epistemology in building science. The concept of science in the Quran, from the point of view of philosophy. Framework used to analyze this theme is the philosophical framework. In the paradigm of philosophy, science concepts can be classified in three dimensions; the first, an epistemological dimension, namely the study of philosophy from the aspect of how to acquire knowledge. Part of this philosophy is called the theory of knowledge, namely methodology to gain knowledge or science, or how to obtain a true knowledge; second, the ontological dimension, namely the branch of philosophy that discusses the object of study of science, or the nature of the study of science; and the third, axiological dimension, namely the branch of philosophy that discusses the purpose and use value and the value of the benefits of science. Part of this philosophy better known as the theory of value. And what about his role in building the Islamic sciences in Islamic universities in particular and in the Islamic world in general. Abstrak: Artikel ini bertujuan untuk mengelaborasi al-QuranÂ sebagai landasan epistemologi dalam membangun sains Islam. Konsep ilmu dalam al-Quran, ditinjau dari sudut pandang filsafat. Kerangka yang dipakai untuk menganalisis tema ini adalah kerangka pemikiran filsafat. Dalam paradigma filsafat, konsep ilmu dapat diklasifikasi dalam tiga dimensi; pertama, dimensi epistemologis, yakni kajian filsafat dari aspek bagaimana cara memperoleh ilmu pengetahuan. Bagian filsafat ini disebut teori ilmu pengetahuan, yaitu metodologi untuk mendapatkan ilmu pengetahuan, atau cara mendapatkan pengetahuan yang benar; kedua, dimensi ontologis, yakni cabang filsafat yang membahas tentang objek kajian ilmu pengetahuan, atau hakikat segala yang menjadi kajian ilmu; dan ketiga, dimensiÂ aksiologis, yakni cabang filsafat yang mem-bahas tentang tujuan dan nilai guna serta nilai manfaat ilmu pengetahuan. Bagian filsafat ini lebih dikenal dengan teori nilai. DanÂ bagaimanaÂ Â peranannya dalam membangunÂ sains Islam di perguruan tinggi IslamÂ Â khususnyaÂ dan di dunia IslamÂ pada umumnya. Keywords: al-Quran, ayat al-matluwah, ayat al-majluwah, al-âilm, al-á¸¥ikmah, dan al-maârifah.